1965
DOI: 10.2307/1934008
|View full text |Cite
|
Sign up to set email alerts
|

Plant Succession on Dune Sands in Fremont County, Idaho

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology. Abstract. Active sand dunes in Fremont County, Idaho, move northe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…The pioneer grass species (green line in Fig. 1) mimics the physiological attributes of marram grass (Ammophila) or scurf-pea (Psoralea lanceolata), which require burial for optimal growth (Chadwick and Dalke, 1965;Van der Putten et al, 1993;Moore, 1996;Van der Stoel et al, 2002), but have relatively short life cycles, so the inferred physiological range [0, 1] does not extend beyond the geomorphic range. Conversely the successional shrub behaviour (red line in Fig.…”
Section: Model Description and Methods Of Landscape Analysismentioning
confidence: 99%
“…The pioneer grass species (green line in Fig. 1) mimics the physiological attributes of marram grass (Ammophila) or scurf-pea (Psoralea lanceolata), which require burial for optimal growth (Chadwick and Dalke, 1965;Van der Putten et al, 1993;Moore, 1996;Van der Stoel et al, 2002), but have relatively short life cycles, so the inferred physiological range [0, 1] does not extend beyond the geomorphic range. Conversely the successional shrub behaviour (red line in Fig.…”
Section: Model Description and Methods Of Landscape Analysismentioning
confidence: 99%
“…Its seed can be disseminated long distances by wind. Rabbitbrush cover usually decreases in the first post-fire year followed by large increases within the third year both from resprouting and seed (Blaisdell 1953;Countryman and Cornelius 1957;Chadwick and Dalke 1965;Young and Evans 1974). However, although rapid re-colonization occurred within the first three years on a late seral Wyoming big sagebrush ecological site, cover increased only slightly above pre-burn levels during the next four to six years (Rhodes and others 2010).…”
Section: Green Rabbitbrushmentioning
confidence: 99%
“…Reports on the response of winterfat are mixed. Several authors reported that sprouting was enhanced by fire (Cottam and Stewart 1940;Blaisdell 1953;Chadwick and Dalke 1965). However, in southwestern Idaho, wildfires resulted in nearly 100% mortality of winterfat (Pellant and Reichert 1983;Groves and Steenhof 1988).…”
Section: Shrubs In the Salt-desert And Desert Shrubmentioning
confidence: 99%
“…Although researchers can measure environmental changes, it is often difficult to determine which aspects of the natural environment are most critical in determining the distribution of a given plant population. The abrupt transition between actively moving desert sand dunes and adjacent stabilized dunes (hereafter referred to as ''ondune'' and ''off-dune'' habitats, respectively) provides a natural laboratory to study the effects of resource heterogeneity on desert plants (Chadwick and Dalke 1965;Hennessy et al 1985;Lei 1998). However, the extent to which plant water status, nutrient status, and water use efficiency change in response to resource differences in this habitat boundary is poorly understood.…”
Section: Introductionmentioning
confidence: 99%